Data relating to the Thesis: Organic carbon across the terrestrial-to-aquatic continuum: Assessing source and delivery processes using a combined fingerprinting and carbon loss modelling approach - Wiltshire, Catherine (Cranfield University, 2023)
Data relating to the Thesis: Organic carbon across the terrestrial-to-aquatic continuum: Assessing source and delivery processes using a combined fingerprinting and carbon loss modelling approach Soil and sediment data from the Loch Davan catchment, Aberdeenshire. Data includes land use specific: n-alkane concentrations n-alkanes compound-specific stable isotopes neutral lipid fatty acids (NLFA) concentrations NLFA compound-specific stable isotopes Carbon, N and bulk stable isotopes
Keywords: 'n-alkanes'; 'neutral lipid fatty acids'; 'Carbon and nitrogen content'; 'Compound-specific Isotopes'; 'land-use specific'